KARAKTERISTIK EKOLOGI DAN ASPEK SILVIKULTUR EBONI (Diospyros celebica Bakh.) SULAWESI SELATAN - Baharuddin Nurkin; Amran Achmad; Ngakan Putu Oka; Wirianto Rachman; Samuel A Paembonan (Research Center for Biology-Indonesian Institute of Sciences, 2002)
This paper describes the ebony (Diospyros celebica Bakh.)site characteristics in Amaro Forest,Barru District, South Sulawesi including its secondary succession to create a favourable conditions for stand establishment. Association analysis shows that a wide variety of lowland species have been identified grows together with the ebony.Physical characteristics rather than chemical fertility of soils show a great value in supporting ebony stand growth.Poor stand with low natural regeneration of these remaining fragmented forests suggest the need to apply enrichment planting and improvement cutting to increase their productivity.